The management of menopausal symptoms in women following treatment for cancer at a specialist menopause service. Issue 3 (September 2021) - Chakrabarti, R; Holloway, D; Bruce, D; Rymer, J
Objective: The aim of this study was to identify prescribing patterns at a specialist menopause service in a central London teaching hospital for women following treatment for a malignancy. Study design: This was a prospective cohort study with data collected over a seven-month period from December 2019 to June 2020. All women reviewed at the specialist menopause services following treatment of a malignancy, BRCA carriers and Lynch syndrome were included in the study, with management options divided into three categories: hormonal, non-hormonal and no treatment. Main outcome measures: The primary outcome of this study was to identify prescribing patterns for all women reviewed following a diagnosis of a malignancy, as well as those with genetic mutations necessitating risk-reducing prophylactic bilateral salpingo-oopherectomy (BSO). Results: Altogether 71 women were included in this study, with the majority of women post management of a non-gynaecological malignancy (51/71, 72%), of which breast cancer was the most common (37/71, 52%). While non-hormonal treatment was the most popular among those treated for breast cancer, for all other malignancies, hormonal treatment was more widespread. Fourteen women also had genetic mutations, with all of these women commencing hormonal treatment post risk reducing surgery. Conclusion: With the exception of those with a history of hormone-sensitive breast cancer, the use of hormonal treatment for menopausal symptoms remained widespread. While this was a relatively small study, the need for long-term follow-up across specialist menopause services, to assess the risk of recurrence is vital.